Eye-Tracking in the Study of Visual Expertise: Methodology and Approaches in Medicine - Fox, Sharon Elizabeth; Faulkner-Jones, Beverly Elizabeth (Frontline Learning Research, 2017)
Eye-tracking is the measurement of eye motions and point of gaze of a viewer. Advances in this technology have been essential to our understanding of many forms of visual learning, including the development of visual expertise. In recent years, these studies have been extended to the medical professions, where eye-tracking technology has helped us to understand acquired visual expertise, as well as the importance of visual training in various medical specialties. Medical decision-making involves a complex interplay between knowledge and sensory information, and the study of eye-movements can reveal the mechanisms involved in acquiring the visual component of these skills. Eye-tracking studies have even been extended to develop computational models of procedures for “expert” skill assessment, and to eliminate potential sources of error in image-based diagnostics. This review will examine the current eye-tracking frontier for the study of visual expertise, with specific application to medical professions.